On Semantic and Motivationsl Reconstruction of Russian Dialect Word LUTONYA - E. A. Borisova (Научный диалог, 2018)
The question of the origin of Russian dialect word lutonya recorded by dialectal dictionaries in several meanings related to personal characteristics of the man: ‘slow man,’ ‘scruffy man,’ ‘liar,’ ‘tall man’ is considered. The assumption of belonging of the lexeme to a derivational family of the root lut -, derivatives of which calling linden, linden bark and objects made of linden, is proved. It is noted that in the dialects the meanings of the word lutonya broadly correspond to the semantic models that are typical for synonymous lexemes, and therefore motivationally proved. However, the suffix - on - which can be found if lutonya is a derivative from the root lut -, is not found in “subject” tokens. This observation suggests an effect on the form of the word of folk etymology rapprochement with diminution name Lukyan (variant lutonya is proposed by onomasts along with Lutokha , Lutosha and othres). The author points out that the name Lutonya belongs to the character of folk tales, while there is no direct correspondence between the qualities of the character and the given dialect meanings of the lexeme lutonya . It is suggested that, at the formal level, a well-known folk text may support the functioning of the lutonya appellative.